The Relevance of Primary EU Law on Direct Tax Matters: Lessons From Transfer Pricing Cases - Károlyi, Balázs (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter deals with the relationship of EU law and tax sovereignty of the Member States and serves as an introduction to the national chapters. Given its introductory character, it will provide a general overview of the relevant EU legislation that affects the most the tax sovereignty of the Member States. The main focus of the chapter will be put on primary EU law (leaving the specific issues of harmonization to the national chapters) with particular regard to the recent transfer pricing cases in the light of the EU State aid rules. These cases can demonstrate very well the interdepending relationship between primary EU law and the delicate concept of tax sovereignty of the Member States and that of tax competition in a multilayered legal environment. Keywords: tax sovereignty, fundamental freedoms, fiscal state aid, transfer pricing, tax rulings, tax competition, tax harmonization, profit shifting, tax avoidance, discrimination